Perceptions of the College Experience African American Students on a Predominantly White Campus or a Qualitative Piece of the Retention Puzzle - Davis, R. Deborah ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1995)
Eighteen black students were asked their perceptions of life on a predominantly white university campus, Syracuse University (New York). Data from interviews were analyzed as well as accounts in the campus newspaper during the 5-year period 1988-1993 and interviews with four administrators who worked with minority students in an academic support capacity. Nine of the students had participated in the 1989 pre-college summer program. Students were interviewed in their sophomore year and again in their senior year. Extensive quotes from the interviews support the analysis which covered initial impressions of the university, reactions to the summer program, the college experience, and their feelings of difference. Three major themes surfaced: (1) student identity/development; (2) social interactions; and (3) academic interactions. It was the students' perception that getting through college and interacting with faculty are more difficult for students of color, than for students of the majority culture. All the students interviewed mentioned racism and having been affected by it either in a classroom, an administrative office, or an incident with students on campus. (Contains 56 references.)
ERIC Note: Paper presented at the Annual Conference for Recruitment and Retention of Minorities in Education (9th, Syracuse, NY, April 9-11, 1995).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Black Students; Educational Discrimination; Higher Education; Racial Discrimination; Racial Identification; Racial Relations; Social Integration; Student Attitudes; Student Development; African Americans -- Syracuse University NY; Reports, Research; Speeches/Meeting Papers